Analisis Pembelajaran Matematika Menggunakan Vlog Pada Masa Pandemi (Studi Kasus di SMA Negeri 1 Wuryantoro) - Broto Apriliyanto (Yayasan Pendidikan Penelitian Pengabdian Algero, 2022)
This research is a quantitative descriptive study conducted at SMA N 1 Wuryantoro which conducts the online learning process in teaching and learning activities with the aim to find out online learning in math learning during the covid-19 pandemic. The data collection technique used is an online questionnaire sheet. The subjects in the study were high school student N 1 Wuryantoro. The results of this study showed that learners are actively involved in learning Mathematics using Vlogs, this is indicated by video products that are done according to the set deadline. This includes the preparation of themes, equipment and venues, as well as an understanding of the concepts used in the presentation. Learners' learning interest in learning using Vlogs tends to increase, this is indicated by students' creativity in displaying the results of vlogging videos that they will post on social media.